1989
DOI: 10.1002/fut.3990090202
|View full text |Cite
|
Sign up to set email alerts
|

Cross hedging the Italian Lira/US dollar exchange rate with deutsch mark futures

Abstract: he recent volatility of the Italian lira/US dollar exchange rate introduces a sub-T stantial exchange rate risk for traders and investors with a portfolio including the two currencies. As will be explained later, due to foreign exchange controls in Italy, this risk can be managed using a rather limited set of traditional instruments. From this situation emerges the importance of investigating new exchange rate hedging strategies. The objeztive of this paper is to assess the empirical performance of a strategy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Eaker et al (1993) examined simple, multiple, portfolio, and commodity cross hedges, and showed that for the major currencies, cross hedging offered opportunities for risk reduction but was less effective than traditional similar-asset hedges. However, in assessing the U.S. dollar performance of a hedging strategy where German mark futures were used to cross hedge the Italian lira, Braga, Martin, and Meilke (1989) found, using stochastic dominance rules to assess out-of-sample trading results, that, on average, the German mark cross-hedge strategy was much cheaper than the traditional forward market hedge. Kroner and Sultan (1993) confirm that currency hedging can significantly improve portfolio returns and that more optimum hedge ratios can be estimated 3 In its simplest form cross hedging entails the use of a futures contract in only one commodity or instrument; multiple cross hedging involves the use of futures contracts in more than one commodity.…”
Section: Cross-hedging Currency Risksmentioning
confidence: 99%
See 2 more Smart Citations
“…Eaker et al (1993) examined simple, multiple, portfolio, and commodity cross hedges, and showed that for the major currencies, cross hedging offered opportunities for risk reduction but was less effective than traditional similar-asset hedges. However, in assessing the U.S. dollar performance of a hedging strategy where German mark futures were used to cross hedge the Italian lira, Braga, Martin, and Meilke (1989) found, using stochastic dominance rules to assess out-of-sample trading results, that, on average, the German mark cross-hedge strategy was much cheaper than the traditional forward market hedge. Kroner and Sultan (1993) confirm that currency hedging can significantly improve portfolio returns and that more optimum hedge ratios can be estimated 3 In its simplest form cross hedging entails the use of a futures contract in only one commodity or instrument; multiple cross hedging involves the use of futures contracts in more than one commodity.…”
Section: Cross-hedging Currency Risksmentioning
confidence: 99%
“…As in Braga et al (1989), each alternative differs in its payoff. If the first strategy is chosen, the payoff for this unhedged strategy in U.S. dollars per FC is…”
Section: Framework For Assessing Hedging Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem of offshore commodity hedging has been recently analyzed, among others, by Thompson and Bond, and Sheales and Tomek for the case of Australian wheat exports, and Braga and Martin for the case of the EC variable import levy. The problem of cross-hedging the US$/Italian lira exchange rate using the International Monetary Market Deutsche mark futures is analyzed by Braga, Martin, and Meilke (1989), who proved its feasibility and effectiveness for a short lira hedge.5 More general techniques for the estimation of the optimal hedge ratio have been proposed, among others, by Myers and Thompson (1987), Myers (1988), Herbst, Kare, and Caples (1989). Although these approaches constitute interesting suggestions for further empirical work, it may be argued that the complexity of these models represents a substantial barrier to their empirical application, in particular if the target market is rather unsophisticated, as is the 'Practically speaking, an extremely risk averse hedger may not want to consider a speculative position.…”
Section: The Hedge Modelmentioning
confidence: 99%
“…Following Braga, Martin, and Meilke (1989), the IMM Deutsche mark futures are used to hedge the exchange rate risk; eq. (4) may then be written as (4'):…”
mentioning
confidence: 99%